Solitary brain metastasis as an initial manifestation of gall bladder carcinoma - Kamlesh Kumar Harsh (Journal of the Scientific Society, 2015)
Gallbladder cancer is a common malignancy in Northern India, and it accounts for 2-4% of all malignant gastrointestinal tumors. It is an aggressive tumor with early dissemination to liver and lymph nodes and associated with poor prognosis. Systemic metastases from gall bladder carcinoma (Ca) frequently occur; however, metastatic involvement of the central nervous system is rare and late manifestation and remains an ominous sign. Initial presentation of gall bladder Ca with brain metastasis is rare. We report a case of 65-year-old women who initially presented with a solitary brain metastasis from an adenocarcinoma of the gallbladder, which was diagnosed incidentally when the patient presented with headache, vomiting, and right temporal region swelling. Palliative chemotherapy and cranial radiotherapy were prescribed. She is symptom-free from 3 months after the completion of the treatment.